Self-employment: theoretical foundations and problems - R. K. Sabirova; A. K. Dzhumaeva; R. S. Utalieva (Экономика: стратегия и практика, 2020)
This scientific article deals with the issues of self-employment in the labor market of the Republic of Kazakhstan.This article presents the trends in the development of self-employment in Kazakhstan, problems and factors that constrain the pace of development of the labor market. The authors of the article, as a result of self-employment research, reveal the problems of statistical accounting of self-employed citizens in the Republic of Kazakhstan, using the classification of all unformed labor agreements of citizens as «self-employed», which may seek to hide the true size of unemployment in the country.The use of system analysis methods allowed us to identify the features of self-employment development in Kazakhstan. The tasks set in achieving the goals of the article, the conclusions and concepts obtained are based on the methods of logical and comparative analysis. A review of the world and domestic literature on self-employment was conducted.To increase the effectiveness of programs for the development of the labor market, it is pointed out that it is necessary to improve the legal framework for self-employment, clarify the status of the self-employed population, and reduce the unemployment rate with the development of private entrepreneurship. The authors propose to improve practical steps in the regions for tax registration of unregistered persons engaged in business activities and informally employed employees, their involvement in the pension system, social and health insurance.